Speaking Without Listening: Imitating Dissensus in the Agonistic Public Debates in Russian Political Talk-Shows in the 2010s - Weiser, Tatiana (Javnost-The Public, 2020)
The article aims to give an overview of the Russian public communication in the genre of public agonistic debates in the 2010s. This genre is not yet so traditional for Russia considering its long Soviet history where monological authoritarian tradition of the official discourse did not allow for the development of an agonistic culture. Today we say that though the freedom of speech is our privilege and a public value, the main media channels in the country are subject to State control and are subsidised or ideologically influenced by the State. What nevertheless attracts our attention within this monopolised paradigm is the appearance of a new media culture of public dissensus. In this article, I analyse how public agonistic debates function in today’s Russia and whether they really accomplish their purpose of creating a new public culture of plurality and diversity or just imitate it in order to impose the official State ideology.